2012
DOI: 10.1002/cncy.21185
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration of intrapancreatic accessory spleen: Cytomorphologic features and differential diagnosis

Abstract: BACKGROUND: Intrapancreatic accessory spleen (IPAS) is a rare benign lesion of the pancreas that frequently clinically and radiographically mimics a solid neoplasm. Very rarely, epidermoid cysts may form in IPAS and be mistaken for a cystic neoplasm of the pancreas on radiographic imaging. IPAS and epidermoid cyst involving intrapancreatic cyst (ECIPAS) are benign, and, if recognized, do not require surgical intervention. There are few reports of the cytopathologic features of IPAS diagnosed by fine‐needle asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…Tatsas et al reported 6 cases with a suspected intrapancreatic accessory spleen (IPAS) who underwent EUS-FNA (40). Of these 6 cases, IPAS was histologically confirmed for 3 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Tatsas et al reported 6 cases with a suspected intrapancreatic accessory spleen (IPAS) who underwent EUS-FNA (40). Of these 6 cases, IPAS was histologically confirmed for 3 cases.…”
Section: Discussionmentioning
confidence: 99%
“…[1] IPAS is a benign congenital lesion of the pancreas that results from entrapment of portion of the spleen in the dorsal pancreatic bud during embryologic development. [23] IPAS affects approximately 10% of the population with 15%–20% of the cases present in the tail of the pancreas. [23] IPASs are usually incidentally discovered due to increased use of sophisticated imaging studies.…”
Section: Brief Review Of the Topicmentioning
confidence: 99%
“…[23] IPAS affects approximately 10% of the population with 15%–20% of the cases present in the tail of the pancreas. [23] IPASs are usually incidentally discovered due to increased use of sophisticated imaging studies. IPAS does not require surgical intervention unless it is involved by a secondary process, such as benign disease or malignancy.…”
Section: Brief Review Of the Topicmentioning
confidence: 99%
See 2 more Smart Citations